Síntese e caracterização de hidrogéis de celulose bacteriana da kombucha - Serpa, Evelin Thayná Barbosa (Universidade Federal de São Carlos, 2026)
The growing environmental concern has driven the use of biopolymers as sustainable alternatives to conventional materials, with bacterial cellulose (BC) standing out due to its high purity, biodegradability, biocompatibility, and absence of cytotoxicity. Unlike plantderived cellulose, its production does not require harsh processing steps, such as the removal of lignin and hemicellulose using strong acids and alkalis. Furthermore, its structure, composed of a highly hydrated nanofibrillar network, allows it to be classified as a type of hydrogel, although there are divergences in the literature regarding this definition.In this context, this study aimed to utilize waste from Kombucha production to obtain bacterial cellulose (KBC) and apply it in the production of biodegradable hydrogels. KBC production was carried out using a 2³ factorial design, evaluating sugar concentration, sugar type, and cultivation time, with membrane thickness as the response variable. The results indicated that cultivation time (21 days) was the most significant factor (89.68%), while sugar-related variables did not show a significant effect at this stage.KBC was used to produce environmentally friendly hydrogels, which were crosslinked with carboxymethylcellulose and calcium chloride (CMC/CaCl₂) and with citric acid (CA), using two approaches: defibrillated and intact structures. The KBC and hydrogel samples were characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TG), X-ray diffraction (XRD), and scanning electron microscopy (SEM). The hydrogels were also subjected to swelling tests, and their crosslinking densities were determined.FTIR and TG analyses confirmed the occurrence of crosslinking and the formation of chemical bonds, while XRD indicated the preservation of the cellulose crystalline structure. SEM images revealed that sugar concentration influences the density of the polymeric network, directly affecting swelling properties. Swelling tests and crosslinking density analysis demonstrated that water absorption behavior is directly related to the type of sugar used. The best results were obtained with demerara sugar, especially at a concentration of 10%, with swelling values of 3,900% for the citric acid-crosslinked hydrogel (HCA) and 30,000% for the CMC/CaCl₂-crosslinked hydrogel (HCMC), indicating the formation of less densely crosslinked networks with higher absorption capacity.The results demonstrate the potential of KBC and the developed hydrogels for environmental applications, particularly in wastewater treatment, heavy metal removal, and sustainable superabsorbent systems.
Synthesis and characterization of cellulose hydrogels bacterian kombucha
Keywords: Biopolímeros; Hidrogéis biodegradáveis; Kombucha; Biopolymer; Biodegradable hydrogels; CIENCIAS EXATAS E DA TERRA::QUIMICA; 15. Vida Terrestre; 12. Consumo e Produção Responsáveis